2023
DOI: 10.3389/fimmu.2023.1220760
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of cuproptosis-related lncRNAs associated with pancreatic cancer immune microenvironment based on single-cell

Yimeng Sun,
Lin Yao,
Changfeng Man
et al.

Abstract: BackgroundCuproptosis, a novel mode of cell death associated with the tricarboxylic acid (TCA) cycle, is relevant to the development of cancer. However, the impact of single-cell-based Cuproptosis-associated lncRNAs on the Tumor immune microenvironment (TIME) of Pancreatic adenocarcinoma (PAAD) and its potential value for individualized immunotherapy has not been clarified.Methods14 immune-related CRGs were screened by exploring the interaction between differentially expressed Immune-Related Genes (IRGs) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Despite advances in diagnostics and therapeutics, PC remains a very challenging condition to treat, with consistently high mortality rates and limited available treatments 40,41 . Recently, research has focused on identifying prognostic markers for PC, and preclinical studies have identified several prognostic lncRNA signatures 8,[42][43][44] . LncRNAs have been further suggested to have implications in diagnosis, drug resistance, and therapeutics in PC 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in diagnostics and therapeutics, PC remains a very challenging condition to treat, with consistently high mortality rates and limited available treatments 40,41 . Recently, research has focused on identifying prognostic markers for PC, and preclinical studies have identified several prognostic lncRNA signatures 8,[42][43][44] . LncRNAs have been further suggested to have implications in diagnosis, drug resistance, and therapeutics in PC 4 .…”
Section: Discussionmentioning
confidence: 99%